International dimensions of Portuguese late colonialism and decolonization [Special Issue] - Jerónimo, Miguel Bandeira (2013)
The present volume, International Dimensions of Portuguese Late Colonialism and Decolonization, offers a multifaceted approach to the role played by international factors and processes in Portuguese late colonialism. In identifying and assessing some of its main manifestations, it explores their relation with metropolitan and colonial historical events and dynamics. Its six original articles examine the ways in which Portugal (and its authoritarian regime) interacted with the fundamental transformations that characterized the international arena after World War II, especially those impacting on imperial and colonial formations, on their late evolution, and eventual demise. The chronological boundaries of this volume correspond to the major transformations of the international regime that resulted from the War, that is, from the constitution of the United Nations system (and in acknowledging the important changes brought after 1945 one must stress the fundamental legacy of the League of Nations in relation to imperial and colonial questions) to the zenith of the decolonization process in Portuguese Africa, the formal dissolution of its colonial empire.